Core-shell structure porous polymer-carbon nanotube filter membrane and preparation method thereof
Conjugated microporous polymer-carbon nanotube filter membrane prepared by cross-coupling reaction under metal catalysts solves the inefficiency of traditional air purifiers in capturing fine particles less than 1 μm and the easy material in high temperature and humid environments The damage problem has achieved efficient and stable air filtration performance.
Patent Information
- Application Number
- CN202411592763.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art is difficult to effectively capture fine particulate matter (PM) with a diameter less than 1 μm. The capture efficiency of traditional air purifiers in this size range is low, and traditional membrane materials are easily damaged in high temperature and humid environments, making it difficult to achieve large-scale commercialization.
Free radical addition is used to prepare bromine functionalized multi-wall carbon nanotubes, and cross-coupling reaction with functional blocks under metal catalysts to form core-shell structure composite materials, and conjugated micropores are prepared by vacuum suction filtration and freeze-drying. Polymer-carbon nanotube filter membrane with excellent porosity and adsorption sites.
It has achieved efficient filtering of fine particulate matter, with large specific surface area, hierarchical porous structure, processability and good gas flow and mass transfer efficiency. It is suitable for air filtration in complex environments, and has a simple preparation process and mild conditions.
Smart Images

Figure CN119281138A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of core-shell structure filtration membranes, and in particular to a core-shell structure porous polymer-carbon nanotube filtration membrane and a preparation method thereof. Background Art
[0002] Particles with aerodynamic diameters less than 10 μm and 2.5 μm (PM 10 and PM 2.5 ) Due to their small size, they can enter the respiratory tract and lungs and cause harm to human health. Fine particles with a diameter of less than 1μm can enter the alveoli like gas molecules, and even enter the heart, liver, kidneys, brain and other extrapulmonary tissues through the circulatory system. The various sources of PM include vehicle and industrial emissions, the combustion of biomass and coal, and other natural or human activities, making the composition of PM complex. Traditional air purifiers can effectively remove PM 10 and PM 2.5 However, for particles with a diameter in the range of 0.1-1 μm, the capture efficiency is greatly reduced due to the inertial impact being insignificant due to their small size. Therefore, how to effectively capture PM with a diameter less than 1 μm is a global focus and a very challenging problem.
[0003] Membrane separation technology is the most effective and direct method for filtering and capturing PM in complex environments, and has significant advantages over traditional separation methods such as adsorption or absorption. This technology has significant advantages in terms of high energy efficiency, low investment, environmentally friendly process, and continuous operation, surpassing other traditional energy-intensive separation materials. The key and difficulty of membrane materials lies in optimizing the adsorption performance, permeability, mechanical stability, and environmental tolerance of the membrane. Extensive research divides existing membrane materials into three categories: polymer membranes, inorganic membranes, and composite membranes composed of polymers and fillers. (1) Polymer membranes have attracted widespread attention due to their cost-effectiveness, special membrane processing characteristics, and excellent separation performance. However, polymer membranes strive to strike a balance in the trade-off relationship between permeability and selectivity (Robeson upper bound) to ensure the economic competitiveness of membrane-based gas separation processes. In addition, the gas separation polymer membranes currently used are extremely susceptible to significant plasticization and degradation due to environmental temperature / humidity fluctuations and exposure to acidic and alkaline vapors. (2) Inorganic membranes made of zeolites, silica, metals, and metal-organic frameworks (MOFs) are promising candidate materials due to their precisely defined porosity, excellent permeability, and superior selectivity. However, the large-scale commercialization of inorganic membranes is hampered by the complex production process, easy degradation in humid / acidic and alkaline environments, and inherent brittleness during regeneration.
[0004] Incorporating organic fillers into polymer matrices to form composite membranes has become the best alternative, combining the processability advantages of inorganic matrices with the pore properties and tunable structures of organic polymers. With the advancement of materials science research, more and more porous materials such as covalent organic frameworks (COFs), porous organic cages (POCs), and conjugated microporous polymers (CMPs) have been designed and developed to prepare defect-free membrane materials with excellent filtration and permeation properties. CMPs have kinetic diameters close to the molecular scale and are expected to achieve size-selective membrane separations thanks to their controllable chemical functions and tunable pore structures. The physical and chemical properties, micromorphology, and pore structure of CMPs can be effectively controlled by controlling the type and length of structural units, optimizing polymerization conditions, and fine-tuning the monomer composition. In addition, due to their rigid conjugated framework and inherent superhydrophobicity, CMPs exhibit excellent resistance to acids, bases, organic vapors, and water vapor in adsorption and filtration applications. This effectively solves the problem of structural collapse and decomposition of membrane materials under high temperature and humid environments, thereby meeting the technical prerequisites for the capture process. It is worth noting that using carbon nanotubes (CNTs) as substrates effectively solves the problem of CMPs being difficult to form membranes. The three-dimensional network structure of CNTs can significantly reduce the permeation resistance of the membrane and alleviate the trade-off between permeation resistance and separation selectivity in the composite membrane without affecting the specific surface area and pore volume. Summary of the invention
[0005] Purpose of the invention: To meet the demand for high-efficiency air filtration materials, the present invention adopts free radical addition to prepare bromine-functionalized multi-walled carbon nanotubes, mixes them with functional building blocks and structural building blocks, and prepares a core-shell structure composite material with excellent pore properties and abundant adsorption sites through cross-coupling reaction under metal catalysts, and prepares a conjugated microporous polymer-carbon nanotube composite filter membrane through vacuum filtration and freeze drying. The filter membrane not only has a series of advantages such as large specific surface area, hierarchical porous structure, processability, and excellent filtration performance, but also has good gas circulation and mass transfer efficiency. The preparation process is simple and the conditions are mild. It is a high-performance air filtration material with broad application prospects.
[0006] The present invention provides a core-shell structure porous polymer-carbon nanotube filter membrane and a preparation method thereof, comprising the following steps:
[0007] Step S1, preparing bromine-functionalized multi-walled carbon nanotubes: under an argon environment, adding multi-walled carbon nanotubes MWCNTs and bromoaniline into a round-bottom flask equipped with a reflux condenser and a magnetic stirring bar, slowly adding isoamyl nitrite, heating and vigorously stirring, to prepare bromine-functionalized multi-walled carbon nanotubes;
[0008] Step S2, preparing a core-shell structure composite material: dissolving bromine-functionalized multi-walled carbon nanotubes in a reaction solvent containing bromine-functional building blocks and alkyne-functional building blocks, heating and continuously reacting under a metal catalyst, and then performing solvent replacement and Soxhlet extraction to prepare a core-shell structure composite material;
[0009] Step S3, preparing a core-shell structure porous polymer-carbon nanotube filter membrane: the cleanly replaced core-shell structure composite material is vacuum filtered and freeze-dried to prepare a core-shell structure porous polymer-carbon nanotube filter membrane with a smooth surface without defects and excellent pore properties.
[0010] In step S1, the bromoaniline is at least one of 4-bromoaniline, 2-amino-5-bromopyridine, 2-amino-5-bromopyrazine, and 2-amino-5-bromopyrimidine;
[0011] The capacity of the round-bottom flask is 50 mL (a round-bottom flask with a small size has insufficient space during a violent reaction, and a round-bottom flask with a large size cannot achieve the purpose of violent stirring during the reaction. A large number of experiments show that 50 mL has the best effect).
[0012] In step S1, the amount of multi-walled carbon nanotubes MWCNTs used is 25-35 mg, and the amount of isoamyl nitrite used is 1.8-2.2 mL (13.4-16.4 mmol).
[0013] In step S1, during the heating and vigorous stirring, the reaction temperature is 50 to 70° C. and the reaction time is 10 to 14 hours.
[0014] In step S2, the reaction solvent is at least one of toluene, N,N-dimethylformamide, 1-dichloroethane, 2-dichloroethane, and tetrahydrofuran, and the reaction solvent is mixed with triethylamine, and the volume ratio of the reaction solvent to triethylamine is 1:1 to 3:1.
[0015] In step S2, the reaction unit molar ratio of the bromine functional building block to the alkyne functional building block is 1:1 to 2:1.
[0016] In step S2, the continuous heating reaction under the metal catalyst has a reaction temperature of 80 to 100° C. and a reaction time of 48 to 72 hours. The reaction catalysts are tetrakistriphenylphosphine palladium and cuprous iodide, and the molar ratio of the two catalysts is 1:5 to 1:15.
[0017] In step S2, the solvent replacement uses dichloromethane, chloroform, acetone, deionized water and methanol in sequence, and the Soxhlet extraction uses at least one of methanol, chloroform and dichloromethane.
[0018] In step S3, the freeze-drying temperature is less than or equal to -50°C, the vacuum degree of the vacuum filtration is less than or equal to 100 Pa, the freeze-drying time is 8 to 12 hours, the obtained porous polymer shell layer has a thickness of 3 to 5 nm, and the filter membrane size is 5 cm.
[0019] The present invention also provides a core-shell structure conjugated microporous polymer-carbon nanotube composite filter membrane, which is prepared by the method described above and can be applied to complex environments to stably intercept and remove harmful particles.
[0020] Beneficial effects: The present invention provides a core-shell structure porous polymer-carbon nanotube filter membrane and a preparation method thereof, wherein bromine-functionalized multi-walled carbon nanotubes are prepared by free radical addition, mixed with functional building blocks and structural building blocks, and cross-coupling reaction is performed under a metal catalyst to prepare a core-shell structure composite material with excellent pore properties and abundant adsorption sites, and a multi-polymer-carbon nanotube filter membrane is prepared by vacuum filtration and freeze drying. The porous polymer shell layer of the filter membrane has a thickness of 3-5 nm and a specific surface area of 121-167 m 2 / g, the average pore size is 1.83-2.51nm, the PM filtration efficiency is 85.6-97.9%, and the air resistance is lower than 118Pa. It not only has a series of advantages such as large specific surface area, graded porous structure, machinability, and excellent filtration performance, but also has good gas circulation and mass transfer efficiency. The preparation process is simple and the conditions are mild. It is a high-performance air filtration material with broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0022] Figure 1 is a scanning electron microscope image of the microporous polymer-carbon nanotube filtration membrane in Example 1.
[0023] Figure 2 is a transmission electron microscope image of the microporous polymer-carbon nanotube filtration membrane in Example 1.
[0024] Figure 3 This is the Fourier transform infrared spectrum of the microporous polymer-carbon nanotube filter membrane in Example 1.
[0025] Figure 4 This is the powder X-ray diffraction spectrum of the microporous polymer-carbon nanotube filter membrane in Example 1.
[0026] Figure 5 This is the surface element distribution diagram of the microporous polymer-carbon nanotube filtration membrane in Example 1.
[0027] Figure 6 Schematic diagram of a scanning electron microscope image of the microporous polymer-carbon nanotube filtration membrane in Example 2.
[0028] Figure 7 Schematic diagram of the transmission electron microscope image of the microporous polymer-carbon nanotube filter membrane in Example 2.
[0029] Figure 8 This is the Fourier transform infrared spectrum of the microporous polymer-carbon nanotube filter membrane in Example 2.
[0030] Fig. 9 This is the powder X-ray diffraction spectrum of the microporous polymer-carbon nanotube filter membrane in Example 2.
[0031] Fig.10 Schematic diagram of a scanning electron microscope image of the microporous polymer-carbon nanotube filtration membrane in Example 3.
[0032] Fig.11 Schematic diagram of the transmission electron microscope image of the microporous polymer-carbon nanotube filter membrane in Example 3.
[0033] Fig.12 Schematic diagram of the Fourier transform infrared spectrum of the microporous polymer-carbon nanotube filter membrane in Example 3.
[0034] Fig.13 Schematic diagram of a scanning electron microscope image of the microporous polymer-carbon nanotube filtration membrane in Example 4.
[0035] Fig.14 Schematic diagram of the transmission electron microscope image of the microporous polymer-carbon nanotube filter membrane in Example 4.
[0036] Fig.15 Schematic diagram of the Fourier transform infrared spectrum of the microporous polymer-carbon nanotube filter membrane in Example 4.
[0037] Fig.16 It is a flow chart of the method of the present invention. DETAILED DESCRIPTION
[0038] Example 1
[0039] like Fig.16 As shown, this embodiment provides a method for preparing a core-shell structure porous polymer-carbon nanotube filter membrane, comprising the following steps:
[0040] S11. Preparation of bromine-functionalized multi-walled carbon nanotubes: MWCNTs (30 mg) and 2-amino-5-bromopyrazine were added to a 50 mL round-bottom flask equipped with a reflux condenser and a magnetic stirring bar. Isoamyl nitrite (2 mL, 14.9 mmol) was slowly added, and then the system was heated to 60 °C and vigorously stirred at this temperature for 12 hours to prepare bromine-functionalized multi-walled carbon nanotubes;
[0041] S12. Preparation of core-shell structure composite materials: Place a mixture of bromine-functionalized multi-walled carbon nanotubes prepared in S11, 1,10-phenanthroline-5,6-dione and 3,8-dibromo-2,4,6-tri-4-ethylphenyl-1,3,5-triazine (molar ratio 1:1) and anhydrous DMF in a round-bottom flask. Add dry triethylamine (the volume ratio of DMF to triethylamine is 2:1), tetrakistriphenylphosphine palladium and cuprous iodide (molar ratio 1:10) and react at 90°C under argon for 72 hours. Replace the solvent with dichloromethane, acetone, deionized water and methanol in turn, and further Soxhlet extraction with methanol for 48 hours to prepare a core-shell structure composite material;
[0042] S13. Preparation of core-shell structure porous polymer-carbon nanotube filtration membrane: The composite material prepared in S12 was vacuum filtered and freeze-dried (freeze-drying temperature -55 ° C, vacuum degree 50 Pa, freeze-drying time 10 hours) to prepare a core-shell structure porous polymer-carbon nanotube filtration membrane with smooth surface, no defects and excellent pore properties, with a specific surface area of 167m 2 / g, and the average pore size is 1.83nm.
[0043] Figure 1 This is a scanning electron microscope image of the filtration membrane obtained in Example 1, which shows that the material is a three-dimensional network structure in which the surface of multi-walled carbon nanotubes is uniformly wrapped with a porous polymer layer.
[0044] Figure 2 This is a transmission electron microscope image of the filtration membrane obtained in Example 1, which shows that the material is a core-shell structure of an outer porous polymer layer and inner multi-walled carbon nanotubes, and the thickness of the porous polymer layer is 3-5 nm.
[0045] Figure 3 This is the Fourier transform infrared spectrum of the filter membrane obtained in Example 1, which shows that the structure of the material has CN stretching vibration, terminal alkyne (-C≡CH) stretching vibration and C=C, C≡C stretching vibration.
[0046] Figure 4 The powder X-ray diffraction pattern of the filtration membrane obtained in Example 1 shows that the material has a diffraction peak (16°) representing amorphous CMPs and diffraction peaks (27° and 43°) representing multi-walled carbon nanotubes of (002) and (100) crystal planes.
[0047] Figure 5This is the energy dispersion spectrum of the filter membrane obtained in Example 1, which shows the successful preparation of brominated carbon nanotubes and the uniform distribution of carbon, nitrogen and oxygen elements in the composite material.
[0048] In the figure, Transmittance represents transmittance, Wavenumber represents wave number, Intensity represents intensity, and 2Theta represents 2θ diffraction angle.
[0049] Example 2
[0050] This embodiment provides a method for preparing a core-shell structured porous polymer-carbon nanotube filter membrane, comprising the following steps:
[0051] S21. Preparation of bromine-functionalized multi-walled carbon nanotubes: MWCNTs (25 mg) and 4-bromoaniline were added to a 50 mL round-bottom flask equipped with a reflux condenser and a magnetic stirring bar. Isoamyl nitrite (2.2 mL, 16.4 mmol) was slowly added, and then the system was heated to 50 °C and vigorously stirred at this temperature for 14 hours to prepare bromine-functionalized multi-walled carbon nanotubes;
[0052] S22. Preparation of core-shell structure composite materials: Place a mixture of bromine-functionalized multi-walled carbon nanotubes prepared in S21, 1,10-phenanthroline-5,6-dione and 3,8-dibromo-2,4,6-tri-4-ethylphenyl-1,3,5-triazine (molar ratio 1.5:1) and anhydrous toluene in a round-bottom flask. Add dry triethylamine (toluene and triethylamine volume ratio is 1:1), tetrakistriphenylphosphine palladium and cuprous iodide (molar ratio 1:5) and react at 100°C under argon for 48 hours. Replace the solvent with chloroform, acetone, deionized water and methanol in turn, and further Soxhlet extraction with methanol for 48 hours to prepare a core-shell structure composite material;
[0053] S23. Preparation of core-shell structure porous polymer-carbon nanotube filtration membrane: The composite material prepared in S22 was vacuum filtered and freeze-dried (freeze-drying temperature -50 ° C, vacuum degree 100 Pa, freeze-drying time 12 hours) to prepare a core-shell structure porous polymer-carbon nanotube filtration membrane with smooth surface, no defects and excellent pore properties, with a specific surface area of 134m 2 / g, and the average pore size is 2.17nm.
[0054] Figure 6 This is a scanning electron microscope image of the filtration membrane obtained in Example 2, which shows that the material is a three-dimensional network structure in which the surface of multi-walled carbon nanotubes is uniformly wrapped with a porous polymer layer.
[0055] Figure 7 This is a transmission electron microscope image of the filtration membrane obtained in Example 2, which shows that the material is a core-shell structure of an outer porous polymer layer and inner multi-walled carbon nanotubes, and the thickness of the porous polymer layer is 3-5 nm.
[0056] Figure 8 This is the Fourier transform infrared spectrum of the filter membrane obtained in Example 2, which shows that the structure of the material contains CN stretching vibration, terminal alkyne (-C≡CH) stretching vibration, and C=C and C≡C stretching vibration.
[0057] Fig. 9 The powder X-ray diffraction pattern of the filtration membrane obtained in Example 2 shows that the material has a diffraction peak (16°) representing amorphous CMPs and diffraction peaks (27° and 43°) representing multi-walled carbon nanotubes of (002) and (100) crystal planes.
[0058] Example 3
[0059] This embodiment provides a method for preparing a core-shell structured porous polymer-carbon nanotube filter membrane, comprising the following steps:
[0060] S31. Preparation of bromine-functionalized multi-walled carbon nanotubes: MWCNTs (35 mg) and 2-amino-5-bromopyridine were added to a 50 mL round-bottom flask equipped with a reflux condenser and a magnetic stirring bar. Isoamyl nitrite (1.8 mL, 13.4 mmol) was slowly added, and then the system was heated to 70 °C and vigorously stirred at this temperature for 10 hours to prepare bromine-functionalized multi-walled carbon nanotubes;
[0061] S32. Preparation of core-shell structure composite materials: Place a mixture of bromine-functionalized multi-walled carbon nanotubes prepared in S31, 1,10-phenanthroline-5,6-dione and 3,8-dibromo-2,4,6-tri-4-ethylphenyl-1,3,5-triazine (molar ratio 2:1) and anhydrous tetrahydrofuran in a round-bottom flask. Add dry triethylamine (the volume ratio of tetrahydrofuran to triethylamine is 3:1), tetrakistriphenylphosphine palladium and cuprous iodide (molar ratio 1:15) and react at 80°C under argon for 60 hours. Replace the solvent with chloroform, dichloromethane, acetone, deionized water and methanol in turn, and further Soxhlet extraction with dichloromethane for 48 hours to prepare a core-shell structure composite material;
[0062] S33. Preparation of core-shell structure porous polymer-carbon nanotube filtration membrane: The composite material prepared in S32 was vacuum filtered and freeze-dried (freeze-drying temperature -60 ° C, vacuum degree 20 Pa, freeze-drying time 8 hours) to prepare a core-shell structure porous polymer-carbon nanotube filtration membrane with smooth surface, no defects and excellent pore properties, with a specific surface area of 141m 2 / g, and the average pore size is 2.02nm.
[0063] Fig.10 This is a scanning electron microscope image of the filtration membrane obtained in Example 3, which shows that the material is a three-dimensional network structure in which the surface of multi-walled carbon nanotubes is uniformly wrapped with a porous polymer layer.
[0064] Fig.11 This is a transmission electron microscope image of the filtration membrane obtained in Example 3, which shows that the material is a core-shell structure of an outer porous polymer layer and inner multi-walled carbon nanotubes, and the thickness of the porous polymer layer is 3-5 nm.
[0065] Fig.12 This is the Fourier transform infrared spectrum of the filter membrane obtained in Example 3, indicating that the structure of the material contains CN stretching vibration, terminal alkyne (-C≡CH) stretching vibration, and C=C and C≡C stretching vibration.
[0066] Example 4
[0067] This embodiment provides a method for preparing a core-shell structured porous polymer-carbon nanotube filter membrane, comprising the following steps:
[0068] S41. Preparation of bromine-functionalized multi-walled carbon nanotubes: MWCNTs (30 mg) and 2-amino-5-bromopyrimidine were added to a 50 mL round-bottom flask equipped with a reflux condenser and a magnetic stirring bar. Isoamyl nitrite (2.2 mL, 16.4 mmol) was slowly added, and then the system was heated to 65 °C and vigorously stirred at this temperature for 12 hours to prepare bromine-functionalized multi-walled carbon nanotubes;
[0069] S42. Preparation of core-shell structure composite materials: Place a mixture of bromine-functionalized multi-walled carbon nanotubes prepared in S41, 1,10-phenanthroline-5,6-dione and 3,8-dibromo-2,4,6-tri-4-ethylphenyl-1,3,5-triazine (molar ratio 3:2) and anhydrous 1,2-dichloroethane in a round-bottom flask. Add dry triethylamine (volume ratio of 1,2-dichloroethane to triethylamine is 2:1), tetrakistriphenylphosphine palladium and cuprous iodide (molar ratio 1:10) and react at 90°C under argon for 48 hours. Replace the solvent with chloroform, acetone, deionized water and methanol in turn, and further Soxhlet extraction with methanol for 48 hours to prepare a core-shell structure composite material;
[0070] S43. Preparation of core-shell structure porous polymer-carbon nanotube filtration membrane: The composite material prepared in S42 was vacuum filtered and freeze-dried (freeze-drying temperature -55 ° C, vacuum degree 40 Pa, freeze-drying time 10 hours) to prepare a core-shell structure porous polymer-carbon nanotube filtration membrane with smooth surface, no defects and excellent pore properties, with a specific surface area of 149m 2 / g, and the average pore size is 2.17nm.
[0071] Fig.13 This is a scanning electron microscope image of the filtration membrane obtained in Example 4, which shows that the material is a three-dimensional network structure in which the surface of multi-walled carbon nanotubes is uniformly wrapped with a porous polymer layer.
[0072] Fig.14This is a transmission electron microscope image of the filtration membrane obtained in Example 4, which shows that the material is a core-shell structure of an outer porous polymer layer and inner multi-walled carbon nanotubes, and the thickness of the porous polymer layer is 3-5 nm.
[0073] Fig.15 This is the Fourier transform infrared spectrum of the filter membrane obtained in Example 4, which shows that the material structure has CN stretching vibration, terminal alkyne (-C≡CH) stretching vibration and C=C, C≡C stretching vibration.
[0074] Comparative Example 1 (without adding carbon nanotubes)
[0075] The core-shell structure porous polymer-carbon nanotube filter membrane was prepared by basically adopting the method of Example 1. The difference is that carbon nanotubes are not added as a flexible growth substrate to be mixed with the conjugated microporous polymer monomer in this example. Specifically, 1,10-phenanthroline-5,6-dione and 3,8-dibromo-2,4,6-tri-4-ethylphenyl-1,3,5-triazine (molar ratio 1:1) were dissolved in anhydrous DMF, and dry triethylamine (DMF and triethylamine volume ratio is 2:1), tetrakistriphenylphosphine palladium and cuprous iodide (molar ratio 1:10) were added to react under argon at 90°C for 72 hours; the solvent was replaced with dichloromethane, acetone, deionized water and methanol in turn, and methanol was further Soxhlet extracted for 48 hours, and vacuum filtration and freeze drying (freeze drying temperature -55°C, vacuum degree 50Pa, freeze drying time 10 hours) were used to obtain a conjugated microporous polymer material with a macroscopic state of powder and a microscopic morphology of amorphous structure. The specific surface area of the obtained material is 121m 2 / g, and the average pore size is 2.51nm.
[0076] Comparative Example 2 (Preparation of composite filtration membrane using unmodified multi-walled carbon nanotubes)
[0077] The porous polymer-carbon nanotube filter membrane was prepared by the method of Example 2. The difference is that this example uses multi-walled carbon nanotubes without pre-brominated functional modification and mixed with conjugated microporous polymer monomers. Specifically, a mixture of pure multi-walled carbon nanotubes, 1,10-phenanthroline-5,6-dione and 3,8-dibromo-2,4,6-tri-4-ethylphenyl-1,3,5-triazine (molar ratio 1.5:1) and anhydrous toluene was placed in a round-bottom flask, and dry triethylamine (toluene and triethylamine volume ratio of 1:1), tetrakistriphenylphosphine palladium and cuprous iodide (molar ratio 1:5) were added to react at 100°C under argon for 48 hours. The solvent was replaced with chloroform, acetone, deionized water and methanol in turn, and then Soxhlet extraction was performed with methanol for 48 hours; vacuum filtration and freeze drying (freeze drying temperature -50 ° C, vacuum degree 100 Pa, freeze drying time 12 hours) were used to prepare a filter membrane with a smooth and defect-free macroscopic surface and excellent pore properties, and a microscopic morphology with partial carbon nanotube agglomeration, free conjugated microporous polymer aggregation, and core-shell structure porous polymer-carbon nanotube coexistence. The specific surface area of the obtained material is 147m 2 / g, and the average pore size is 2.39nm.
[0078] Comparative Example 3 (Using single-walled carbon nanotubes as flexible growth substrate)
[0079] The porous polymer-carbon nanotube filtration membrane was prepared by basically adopting the method of Example 3. The difference is that this example uses single-walled carbon nanotubes functionalized with bromine in advance as a flexible growth substrate to be mixed with conjugated microporous polymer monomers. Specifically, single-walled carbon nanotubes (35 mg) and 2-amino-5-bromopyridine were added to a 50 mL round-bottom flask equipped with a reflux condenser and a magnetic stirring bar, and isoamyl nitrite (1.8 mL, 13.4 mmol) was slowly added. The system was heated to 70 ° C and stirred vigorously for 10 hours to prepare bromine-functionalized single-walled carbon nanotubes; a mixture of the prepared bromine-functionalized single-walled carbon nanotubes, 1,10-phenanthroline-5,6-dione and 3,8-dibromo-2,4,6-tri-4-ethylphenyl-1,3,5-triazine (molar ratio 2:1) and anhydrous tetrahydrofuran was placed in a round-bottom flask, and dry triethylamine (the volume ratio of tetrahydrofuran to triethylamine is 3:1), tetrakistriphenylphosphine palladium and cuprous iodide (molar ratio 1:15) were added and reacted at 80 ° C under argon for 60 hours. The solvent was replaced with chloroform, dichloromethane, acetone, deionized water and methanol in turn, and dichloromethane was further used for Soxhlet extraction for 48 hours; a core-shell structured porous polymer-carbon nanotube filtration membrane with a smooth surface, no defects and excellent pore properties was prepared by vacuum filtration and freeze drying (freeze drying temperature -60 ° C, vacuum degree 20 Pa, freeze drying time 8 hours), with a specific surface area of 155m 2 / g, and the average pore size is 2.17nm.
[0080] Structural characterization and performance testing:
[0081] Scanning electron microscope observation: The microstructure of the porous polymer-carbon nanotube filtration membrane was observed by field emission scanning electron microscope (model JSM-7900F, JEOL Ltd.) Figure 1 , Figure 6 , Fig.10 , Fig.13 ).
[0082] Transmission electron microscopy observation: The microstructure of the porous polymer-carbon nanotube filtration membrane was observed by field emission transmission electron microscopy (TECNI G2 TF20, FEI Company, the Netherlands). Figure 2 , Figure 7 , Fig.11 , Fig.14 ).
[0083] Functional group structure test: An infrared spectrometer (model VERTEX 70, Bruker, USA) was used to record the functional groups of the porous polymer-carbon nanotube filter membrane ( Figure 3 , Figure 8 , Fig.12 , Fig.15 ).
[0084] Crystal structure test: The crystal structure of the porous polymer-carbon nanotube filter membrane was recorded using an X-ray spectrometer (model D / Max-2400, Rigaku Corporation, Japan) Figure 4 , Fig. 9 ).
[0085] Surface element distribution test: An energy dispersive X-ray spectrometer (Vario EL, Japan Electronics) was used to record the surface element distribution of the porous polymer-carbon nanotube filter membrane ( Figure 5 ).
[0086] Specific surface area test: The nitrogen adsorption isotherm was measured at 77 K using a gas adsorption instrument (ASAP 2060, Micromeritics, USA).
[0087] Filtration performance test: The filter membrane (area 25cm 2 ) with a gas flow rate of 1 L / min and cigarettes as the source of particles. Each filter set was tested at least 3 different locations and the results were averaged.
[0088] Experimental results: Figure 1 , Figure 5 , Figure 6 , Fig.10 and Fig.13As shown, the conjugated microporous polymer and bromine-functionalized carbon nanotubes are mixed to prepare the filtration membrane, which can realize the in-situ directional coating of the porous polymer layer on the surface of the flexible substrate. In Example 1, a layer of porous material grows uniformly on the surface of the carbon nanotubes, and there is no obvious agglomeration of carbon nanotubes and free conjugated microporous polymers, which shows the controllable synthesis of the composite material. The conjugated microporous polymer grows in a directional and controllable nucleation on the surface of the carbon nanotubes, which greatly improves the specific surface area and pore properties of the filtration membrane and fully exposes the active center.
[0089] like Figure 2 , Figure 7 , Fig.11 and Fig.14 As shown, the conjugated microporous polymer and bromine-functionalized carbon nanotubes are mixed to prepare a filtration membrane, which can achieve the growth of a porous polymer layer on the surface of a flexible substrate to form a core-shell structure. The lattice stripes representing the carbon nanotubes and the porous structure representing the conjugated microporous polymer can be clearly observed. The thickness of the porous polymer layer is about 3-5nm. The conjugated microporous polymer is uniformly and directional coated on the surface of the carbon nanotubes, which does not affect the specific surface area and pore size of the filtration membrane while fully exposing the adsorption sites.
[0090] like Figure 3 , Figure 8 , Fig.12 and Fig.15 As shown in Figure 2, it can be observed that the signals corresponding to the C≡CH and C-Br bonds disappear, indicating that the Sonogashira coupling reaction has completely occurred. -1 The signals observed at 2200 cm-1 correspond to the stretching and bending vibration modes of the CH bonds in the benzene ring; -1 The signal observed at 1660 cm-1 can be attributed to the stretching vibration of the -C≡C- bond; -1 The absorption peak at 1673 cm-1 corresponds to the C=O carbonyl group; the signals corresponding to the triazine groups (C=N and C=C bonds) are at about 1673, 1508, and 1361 cm-1. -1 It was observed at 1.5 Å, indicating the successful in-situ polymerization of conjugated microporous polymer on the surface of carbon nanotubes.
[0091] like Figure 4 and Fig. 9 As shown in Figure 2, the diffraction pattern of MWCNTs shows two peaks at 28° and 43°, corresponding to the (002) and (100) crystal planes of MWCNTs, respectively. The filter membrane shows a broad peak centered at 15° in its diffraction pattern, indicating that it is formed in an amorphous structure under kinetic control.
[0092] Table 1 compares the specific surface area, pore size and filtration performance test results of the porous polymer-carbon nanotube filtration membranes obtained in the examples and comparative examples. Examples 1-4 and comparative examples 2 and 3 have a higher specific surface area (134 m2 / g-167m 2 / g) and a smaller pore size (1.83nm-2.39nm), because the conjugated microporous polymer is uniformly and directional coated on the surface of carbon nanotubes to form a core-shell structure, which fully exposes the specific surface area and pore properties of the porous polymer layer; the specific surface area of comparative example 1 is only 121m 2 / g, and the average pore size is 2.51 nm, which is due to the disordered stacking growth of the conjugated microporous polymer.
[0093] Table 1
[0094]
[0095] The filtration performance of the porous polymer-carbon nanotube filtration membrane is closely related to the specific surface area and pore size. Examples 1-4 with a larger specific surface area have a better performance on PM 0.3 and PM 2.5 The filtration efficiency of the nanofiber membranes is above 96%, and the air resistance is much lower than that of the traditional nanofiber membranes (all ≤91Pa), which truly achieves high efficiency and low resistance. Among them, Example 1 with the highest specific surface area and the smallest pore size performs best in the filtration test, PM 0.3 and PM 2.5 The filtration efficiency of the samples was 97.9% and 99.9%, respectively, which was much higher than that of the comparative examples 1–3 (PM 0.3 and PM 2.5 The filtration efficiency was <94.8%).
[0096] It can be seen that the technical solution proposed in the present invention enables the core-shell structure porous polymer-carbon nanotube filter membrane to have a high specific surface area, a small pore size and a high filtration performance, which is likely due to: (1) the bromine-functionalized multi-walled carbon nanotubes obtained by the free radical addition method have better solubility and dispersibility, providing more binding sites and opportunities for the reaction; (2) the conjugated microporous polymer monomers are uniformly directed and controllably nucleated and grown on the surface of the functionalized carbon nanotubes to form a core-shell structure, so that the active sites are fully exposed without changing the specific surface area and pore size, and fine particles can be effectively filtered; (3) the carbon nanotubes form a three-dimensional network structure by random weaving and arrangement, which greatly improves the unit gas throughput of the filter membrane and improves the gas flow and mass transfer efficiency of the material; (4) both the conjugated microporous polymer and the carbon nanotubes have excellent chemical stability and environmental tolerance, so that the filter membrane has excellent self-film-forming properties and good processability.
[0097] The present invention provides a core-shell structure porous polymer-carbon nanotube filter membrane and a preparation method thereof. There are many methods and approaches to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be considered as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. A method for preparing a core-shell structured porous polymer-carbon nanotube filtration membrane, characterized in that: The following steps are involved: Step S1, preparing bromine-functionalized multi-walled carbon nanotubes: under an argon environment, adding multi-walled carbon nanotubes MWCNTs and bromoaniline into a round-bottom flask equipped with a reflux condenser and a magnetic stirring bar, slowly adding isoamyl nitrite, heating and vigorously stirring, to prepare bromine-functionalized multi-walled carbon nanotubes; Step S2, preparing a core-shell structure composite material: dissolving bromine-functionalized multi-walled carbon nanotubes in a reaction solvent containing bromine-functional building blocks and alkyne-functional building blocks, heating and continuously reacting under a metal catalyst, and then performing solvent replacement and Soxhlet extraction to prepare a core-shell structure composite material; Step S3, preparing a core-shell structure porous polymer-carbon nanotube filter membrane: the cleanly replaced core-shell structure composite material is vacuum filtered and freeze-dried to prepare a core-shell structure porous polymer-carbon nanotube filter membrane with a smooth surface without defects and excellent pore properties.
2. The method according to claim 1, characterized in that In step S1, the bromoaniline is at least one of 4-bromoaniline, 2-amino-5-bromopyridine, 2-amino-5-bromopyrazine, and 2-amino-5-bromopyrimidine; The capacity of the round-bottom flask is 50 mL.
3. The method according to claim 2, characterized in that In step S1, the amount of multi-walled carbon nanotubes MWCNTs used is 25-35 mg, and the amount of isoamyl nitrite used is 1.8-2.2 mL.
4. The method according to claim 3, characterized in that In step S1, during the heating and vigorous stirring, the reaction temperature is 50 to 70° C. and the reaction time is 10 to 14 hours.
5. The method according to claim 4, characterized in that In step S2, the reaction solvent is at least one of toluene, N,N-dimethylformamide, 1-dichloroethane, 2-dichloroethane, and tetrahydrofuran, and the reaction solvent is mixed with triethylamine, and the volume ratio of the reaction solvent to triethylamine is 1:1 to 3:
1.
6. The method according to claim 5, characterized in that In step S2, the reaction unit molar ratio of the bromine functional building block to the alkyne functional building block is 1:1 to 2:
1.
7. The method according to claim 6, characterized in that In step S2, the continuous heating reaction under the metal catalyst has a reaction temperature of 80 to 100° C. and a reaction time of 48 to 72 hours. The reaction catalysts are tetrakistriphenylphosphine palladium and cuprous iodide, and the molar ratio of the two catalysts is 1:5 to 1:
15.
8. The method according to claim 7, characterized in that In step S2, the solvent replacement uses dichloromethane, chloroform, acetone, deionized water and methanol in sequence, and the Soxhlet extraction uses at least one of methanol, chloroform and dichloromethane.
9. The method according to claim 8, characterized in that In step S3, the freeze-drying temperature is less than or equal to -50°C, the vacuum degree of the vacuum filtration is less than or equal to 100 Pa, the freeze-drying time is 8 to 12 hours, the obtained porous polymer shell layer has a thickness of 3 to 5 nm, and the filter membrane size is 5 cm.
10. A core-shell structure conjugated microporous polymer-carbon nanotube composite filtration membrane, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.